PENDAMPINGAN BRANDING DAN PACKAGING UMKM IKATAN PENGUSAHA AISYIYAH DI KOTA MALANG - Dwi Irawan; Muhammad Wildan Affan (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2020)
Muhammadiyah has formed the Aisyiyah Entrepreneurs Association which aims to accommodate the entrepreneurial activities of Aisyiyah members. But in its implementation there are several obstacles that occur that greatly hinder the development of its business. Among them are products that do not yet have attractive branding and packaging to compete in the market. Through community service, we will provide assistance in the management of branding and packaging so that products produced by IPAS are more able to compete in the market with products that already exist. The method used by lectures, discussions and demonstrations. The results show that the selection of product packaging produced by Malang City IPAS is appropriate and IPAS has more attractive branding to be able to compete in the market. KEYWORDS: Branding; IPAS; Packaging